Analisis Tren Dan Sinyal Transaksi Saham Padi Berbasis Moving Average Dan Macd Sebagai Dasar Penyusunan Panduan Praktis Investasi - Primawati Sinaga; Widia Gultom; Depina Br Tumangger; Cristina Martalia Sitepu; Putri Kemala Dewi Lubis (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to analyze trends and trading signals for PT Minna Padi Investama Sekuritas Tbk (PADI) stock using the Moving Average (MA) and Moving Average Convergence Divergence (MACD) indicators, as well as to develop a practical investment guide based on technical analysis. The study employs a quantitative descriptive method with a documentary study approach using secondary data in the form of daily closing prices of PADI shares from January to May 2026. The analysis utilizes the MA20 and MA50 indicators to identify bullish and bearish trends through golden cross and death cross patterns, while the MACD indicator is used to confirm market momentum strength and stock trading signals. The results indicate that the combination of MA and MACD indicators can assist investors in interpreting trend direction, recognizing market momentum, and determining buy and sell signals more systematically. A golden cross supported by a bullish MACD crossover tends to signal potential stock price increases, while a death cross followed by a bearish MACD crossover indicates potential stock price declines. Furthermore, this study successfully developed practical investment guidelines that can help investors understand the technical analysis process more easily and effectively. Thus, the integration of MA and MACD indicators is considered effective as a basis for stock investment decision-making, particularly for novice investors.